2017
DOI: 10.1016/j.anireprosci.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms and sexual precocity in Nellore heifers

Abstract: The aim of this study was to determine the extent (r) of linkage disequilibrium (LD) in the genome of Nellore cattle, and to examine associations between single nucleotide polymorphisms (SNP) and age at first calving (AFC) and early pregnancy (EP) using a panel of high-density SNPs and data from 1182 Nellore females. A total of 13 contemporary groups (CG) were used consisting of farm, season, and year of birth. For genome-wide association analysis, SNPs with a minor allele frequency (MAF)<0.05 and animals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
4
1
2
Order By: Relevance
“…This may be due either to the lack of knowledge regarding the functions of these genes or the existence of non-annotated genes in this region. It is noteworthy that the present study detected association in regions different from that reported by previous studies on the Nelore breed [ 77 79 ]. This can be because of herd particularities, such as the extent of LD, allelic frequencies, sample size, and statistical approaches [ 79 ], in addition to the use of haplotypes in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be due either to the lack of knowledge regarding the functions of these genes or the existence of non-annotated genes in this region. It is noteworthy that the present study detected association in regions different from that reported by previous studies on the Nelore breed [ 77 79 ]. This can be because of herd particularities, such as the extent of LD, allelic frequencies, sample size, and statistical approaches [ 79 ], in addition to the use of haplotypes in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…In Nellore heifers, the APP gene is linked to AFC and early pregnancy, which supports that the regions found in the present study agree with what is found in the literature (Regatieri et al, 2017). Murata and Petersen (2004) stated that the number of APPs may be associated with early diagnosis, and that is information that allows monitoring the health status of a herd.…”
Section: Discussionsupporting
confidence: 91%
“…Cánovas et al (2014) analyzed eight tissues of pre-and post-pubertal Brangus heifers by RNA-Seq and found that hypothalamus samples had the greatest increase in the puberty regulatory genes as compared with the other analyzed tissues (pituitary gland, uterus, endometrium, ovary, liver, muscle and adipose tissue). In addition, several studies with Nelore heifers have shown that single nucleotide polymorphisms provide relevant information to help elucidate which genes affect puberty onset (Costa et al, 2015;Regatieri et al, 2017).…”
Section: Figurementioning
confidence: 99%